KAJIAN PROSES PELAKSANAAN PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KANTOR PERTANAHAN KABUPATEN MINAHASA UTARA (The Study of the Complete Systematic Land Registration (PTSL) Process in the Land Office of North Minahasa Regency) - Bagus Iryanto; Lucia C. Mandey; Caroline B.D. Pakasi (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
This study aims to analyze the implementation and obstacles of Complete Systematic Land Registration (PTSL) at the Land Office of North Minahasa Regency. The study was conducted for 2 months, starting from April to May 2019. The research location was the North Minahasa Regency Land Office. This study used a qualitative analysis method with a descriptive approach. The data collected consisted of primary data and secondary data. Data collection was conducted through interview, observation, and study of documents. The results showed that the implementation of a complete systematic land registration at the North Minahasa Regency Land Office was carried out very well. This was shown by the success of PTSL in North Minahasa Regency. In 2017, 2,460 fields out of 2,500 targeted fields, could be classified into the K1category (certified), while 40 other fields were included in the K3 Category (cannot be certified). In 2018 the target of PTSL increased to 5,500. 3,642 fields out of the target have been realized in the K1 category (certified), 224 fields included in the K3 category (cannot be certified), and 41 fields included in the K4 category (already certified). Constraints experienced by the North Minahasa District Land Office, namely: 1) Lack of adequate human resources, 2) Lack of adequate facilities and infrastructure, 3) Lack of community participation, and 4) Tax costs on land.Keywords: Complete Systematic Land Registration, PTSL, Land Office, North Minahasa Regency